Organizational Commitment, Job Satisfaction, and OCB among PT. XYZ Employees - Armansyah; Rona Tanjung; Ayu Dwi Lestari; Herman (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Organizational Citizenship Behavior (OCB) is a voluntary employee behavior that does not directly cause imbalance, but contributes significantly to organizational effectiveness. This behavior is strongly influenced by internal employee factors, such as commitment to the organization and job satisfaction. This study aims to analyze the relationship between organizational commitment and job satisfaction on OCB among PT. XYZ employees. A quantitative approach with a descriptive-associative design was used in this study. The entire population consisting of 45 employees was taken as a sample using a census technique. Data collection was carried out through a Likert-sized questionnaire (1–5), which had been tested for validity and reliability. The results of multiple linear regression analysis showed that organizational commitment (β = 0.41; p < 0.01) and job satisfaction (β = 0.35; p < 0.01) had a positive and significant partial effect on OCB. Simultaneously, the two variables explained 57.2% of the variation in OCB (R² = 0.572; F = 28.6; p < 0.001). In conclusion, increasing employee commitment and job satisfaction is an important strategy in forming a work culture that supports OCB behavior and increases organizational effectiveness.